(untitled) (International Journal of Health, Animal Science and Food Safety, 2016)
Despite the population of wild ungulates is rapidly growing (Ramanzin et al., 2010) and the Italian production has the predisposition to the high quality food, there is no food supply chain for hunted game in the Italian territory. Consequently, the customers’ demand is met by relevant amount of imported meat from other nearby markets. With the purpose of understanding the opportunities of an Italian new supply chain, the present research aims at the collection of information about hunters and their behavior in order to assess the food safety of their product. The survey was carried out on a sample of 145 hunters of Verbania (Piedmont-Italy), by using self-compiled questionnaire. Results show the interesting potentialities of the area in terms of quantity of salable product. On the other hand, the hunted meat still does not reach adequate hygienic and quality standards to be traded. In fact, the descriptive analysis show that 63% of the hunters do not provide a proper maturation of the meat and 21% of them do not bleed the game just after shooting. Furthermore, 12% of the respondents use cellars or even the garages for the maturation. The wrong behaviors of the hunters are related to their cultural background, which probably represents the most important barrier for a change. Our findings provide important inputs for the development of a real market for this type of meat. Therefore, the research seems to be relevant at both scientific and practical level. It proposes a new conceptual and practical option for a more sustainable development of Italian (and others) mountain areas.